THE PHYSICAL ORIGIN OF FIDELITY ENHANCEMENT IN THE TELEPORTATION PROTOCOL OF AN ARBITRARY TWO-QUBIT STATE UNDER AMPLITUDE-DAMPING NOISE ENVIRONMENT - Van Hop, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2025)
A new analytical expression for the average quantum fidelity of a teleportation protocol for an arbitrary two-qubit state transmitted through an amplitude-damping noise environment has been established. This expression shows that the average fidelity depends not only on the purity measure and the bipartite entanglement measure of each parallel state forming the quantum channel, but also on the multipartite entanglement measure. This entanglement is generated between the qubits of each parallel state when they interact independently with the amplitude-damping environment. Based on this analytical relation, the physical mechanism for enhancing the teleportation protocol’s average quantum fidelity under two distinct amplitude-damping noise scenarios has been elucidated.